Rapid method for determining nitrate utilization by yeasts. - Hopkins, J M (1977)
A test for the nitrate-reductase activity in yeasts has been developed, in which the reaction may be read after only 10 min of incubation. The rapidity of the test is due to the optimization of pH, substrate concentration, and temperature for the reaction.